The Potential Opportunities in International Portfolio Diversification - Heshmat, Nesma (The Arab Journal of Administration, 2019)
This study aims to investigate potential opportunities in international portfolio diversification. The study searches the opportunities for Egyptian investors in the Middle East and North Africa (MENA), European, Asian and United States stock markets. The study investigates the relationship of the Egyptian’s stock market equity indices with world markets through examining the co-integrating behaviour, Granger causality tests, Variance Decompositions and Impulse Responses. A domestic portfolio has been composed to be used as a benchmark in comparing the benefit of international portfolio diversification using the mean-variance Portfolio Optimization (PO) approach. The results reveal that however the Egyptian market is integrated to the world market, there are still some gains could be achieved from international diversification.